PERBANDINGAN METODE PEMBAYARAN PADA HOTEL MORRISSEY SERVICE APARTMENT - Calvin Denovan; Rivera P Sukma (LPPM and Travel Operation Department Universitas Asa Indonesia, 2016)
This study aims to determine the differences between cash and credit payment methods and whether difference between payments using various credit cards payment, such as Amex, Master and Visa. The method used is the Mann-Whitney and Kruskal Wallis by using the data of three years (36 months) from January 2013 to December 2015. The survey result shows that there are significant there are some differences between cash and credit payment methods. Also, the credit card payment rank order from highest usage is Amex Credit, Visa and Master Credit.